Work-related musculoskeletal disorders : prevention report (Luxembourg, 2008)
"Musculoskeletal disorders (MSDs) are the most common work-related problem in Europe - 25 % of the EU-27 workers report suffering from backache and 23 % complain about muscular pains. First, there are preventive steps that have to be taken. But for workers who already have MSDs, the challenge is to maintain their employability, keep them working and, if necessary, reintegrate them into the workplace. The aim of this report is to evaluate the effectiveness of interventions at the workplace and to provide practical examples with respect to successful prevention of MSDs. It focuses mainly on the developments that have taken place since the previous European MSDs Campaign in 2000."